Analysis of Human Resources Competence in the Implementation of SAK EMKM on the Quality of MSME Financial Reports: Combination Method - Fajar Gumelar; Chofiuddin Muchlis; Gatot Wahyu Nugroho (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2022)
This study aims to determine how the application of SAK EMKM in MSME financial reports, the factors that cause MSMEs not to apply SAK EMKM, and to determine the effect of human resource competence in implementing SAK EMKM on the quality of MSME financial reports. 45 MSMEs in Surade District, which is located on Jl. Raya Surade No. 26 Surade-Sukabumi. This study uses a combination method (quantitative and qualitative) with a mixed combination model (concurrent embedded), data collection techniques using questionnaires, interviews, observations and documentation studies, a population of 1250 MSME units with a sample of 45 MSMEs that already have a business license. The data analysis technique used is validity test, reliability test, normality test, classical assumption test (heteroscedasticity test), simple regression test, and hypothesis testing. As well as using qualitative data analysis techniques by conducting interviews with 45 sources who were previously respondents. This research was assisted by SPSS 26 software by generating the conclusion that the competence of human resources in the application of SAK EMKM has a positive effect on the quality of MSME financial reports. variable X (Human Resource Competence in the Application of SAK EMKM) has an effect on variable Y (MSME Financial Quality).